Pengaruh penambahan sari buah naga merah pada yoghurt susu kedelai serta uji aktivitas antibakteri - Melzi Octaviani; Felycia Wardi; Emma Susanti (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2024)
Food is one of the most important needs for humans because it relates to daily nutritional needs. The solution to this problem is to consume food with good nutritional content supported by appropriate food processing innovations. Milk can be drunk directly or processed into various forms of food and drinks with milk-based ingredients, such as yogurt. This study aims to make yogurt products from soy milk using red dragon fruit juice as a substitute for sugar and to test their antibacterial activity in inhibiting Salmonella typhi and Shigella dysenteriae bacteria. This study used a completely randomized design (CRD) with 3 treatments, namely the addition of red dragon fruit juice with concentrations of 5%, 10%, and 15%, 3 replications, and the diffusion method for testing antibacterial activity. The results showed that the best yoghurt formula was obtained from F3 (yoghurt with the addition of 15% concentration of red dragon fruit juice). The panelist hedonic test gives values ranging from slightly like to like for color, aroma, taste, and texture; for organoleptic F3, these are: color (dark pink), taste (sour), texture (liquid-thick), and aroma (typical); pH 3.49; TAT 1.39%; Lactic Acid Bacteria (LAB) 2.09 x 1010 CFU/mL; and also had an average diameter of inhibition of 18.96 mm against Salmonella thypi (P<0.05) and 20.10 mm against Shigella dysenteriae (p<0.05). Soy milk yogurt with the addition of varying concentrations of red dragon fruit juice has antibacterial activity.